Standardization of Optical Coherence Tomography Angiography Imaging Biomarkers in Diabetic Retinal Disease - Vujosevic, Stela (2021)
Optical coherence tomography Angiography (OCT-A) represents a revolution in the noninvasive evaluation of retinal and choroidal circulation especially in detecting early clinical signs of diabetic retinal disease (DRD). With appropriate use, OCT-A characteristics and measurements have the potential to become new imaging biomarkers in managing and treating DRD. Major challenges include (a) provision of standardized outputs from different OCT-A instruments providing standardized terminology to correctly interpret data; (b) the presence of artifacts; (c) the absence of standardized grading or interpretation method in the evaluation of DRD, similar to that already established in fundus photography; and (d) establishing how OCT-A might be able to provide surrogate markers to demonstrate blood retinal barrier breakdown and vascular leakage, commonly associated with DRD. In fact, OCT-A guidelines for DRD are still evolving. The outputs of quantitative OCT-A data offer a unique opportunity to develop tools based on artificial intelligence to assist the clinicians in diagnosing, monitoring, and managing patients with diabetes. In addition, OCT-A has the potential to become a useful tool for the evaluation of cardiovascular diseases and different neurological diseases including cognitive impairment. This article written by the members of Diabetic Retinopathy expert committee of the European Vision Clinical Research network will review the available evidence on the use of OCT-A as an imaging biomarker in DRD and discuss the limits and the current application as well as future developments for its use in both clinical practice and research trials of DRD.